Effectiveness of Guessing Game in Improving Student Speaking Skills - Andi Asdar; Mujahidah (Inovasi Analisis Data, 2024)
Objective: This study aims to determine the effectiveness of using guessing games in enhancing students' speaking skills compared to traditional teaching methods.Method: The study involved 27 students in a single class. Data were collected using pretest and post-test evaluations. In speaking classes, students were taught using guessing games and traditional approaches. The effectiveness of these methods was then compared based on students' performance in the pretest and post-test.Results: The findings revealed a significant improvement in students' speaking skills when taught using guessing games. The data analysis indicated that the students showed greater improvement with the guessing game method than with traditional teaching methods.Novelty: This research contributes to the field of language education by providing evidence that interactive and engaging methods, such as guessing games, can significantly enhance speaking skills. It underscores the importance of using innovative teaching strategies to improve language learning outcomes.Implications: The implications of this research suggest that educators should incorporate interactive and engaging activities like guessing games into their language teaching practices. This approach can lead to more effective learning experiences, increased student motivation, and improved language proficiency.